Copyright Assessment of The Oral Tradition of Making Fishing Traps Among Indigenous Peoples - Pariela, Marselo Valentino Geovani; Saija, Ronald; Pical, Venda Jolanda; Demmatacco, Triska (Batulis Civil Law Review, 2025)
Introduction: The passing on of traditions from the older generation to the younger generation is generally conveyed scientifically by word of mouth which is carried out with continuous practice, so that usually an oral tradition cannot be verified academically-scientifically but can be accepted as recognition by an indigenous community as a historical fact.  Oral culture or oral tradition is a culture in which writing has not been developed for the purpose of keeping records and passing down knowledge and history.Purposes of the Research: To examine the copyright registration for the oral tradition of making fish traps among indigenous communities on the island of Ambon to obtain recognition of intellectual property rights.Methods of the Research: The research method used is in accordance with the research objectives where the type of research used is sociolegal (sosiolegal research) namely a research method combining doctrinal legal research and empirical legal research methods.Results Main Findings of the Research: Protection of traditional knowledge (oral traditions regarding the creation of traditional fish traps) can prevent the cultural identity of the community that owns it from being lost in line with the extinction of traditional knowledge. Procedure Copyright is one part of intellectual property which has the broadest scope of protected objects, because it includes science, art and literature (art and literacy) which also includes the oral tradition of making fishing traps.